Seaweed-Associated Diatoms (Bacillariophyta) in Dokdo of South Korea: I. Subphyla Melosirophytina, Coscinodiscophytina, and Class Mediophyceae - Joon Sang Park; Kyun-Woo Lee; Seung Won Jung; Han Jun Kim; Jin Hwan Lee (Diversity)
Dokdo is an island located in the easternmost part of Korea, which has high levels of biodiversity of birds and fish, especially marine invertebrates. However, the biodiversity of microalgae, especially diatoms (Bacillariophyta), is relatively unknown, despite their ecological importance as primary producers of the marine food web and bioindicators of environmental conditions associated with climate change. To understand the biodiversity of seaweed-associated diatoms from Dokdo, we collected macroalgae present at a depth 5–15 m by SCUBA diving on 17 October 2017. There were a large number of diatoms (over 130 species), even though it was a one-time survey. As it includes too many taxa to cover at once, voucher flora for other taxonomic groups will be provided through the continuous serial papers. This is the first series of seaweed-associated diatoms, with 26 species belonging to the subphyla Melosirophytina and Coscinodisophytina, and the class Mediophyceae. Among these, seven species including one new taxon were reported for the first time in Korea, which, along with the geopolitical characteristics of the survey area, proved that there is no domestic interest in seaweed-related diatoms. In particular, the appearance of species that have been reported in subtropical waters, such as the order Ardissoneales, requires continuous monitoring of marine seaweed-associated diatoms to confirm whether their colonization in Dokdo waters was due to climate change or species-specific water temperature tolerance.